Biological Modification of Sunn Hemp Fibers with Bacterial Cellulase - Sharma, Dr. Anup Kumar; Kalia, Susheel; Marmat, Adarsh (Asian Journal of Pharmaceutical Research and Development, 2014)
This research articles deals with the bacterial treatment of sunn hemp fibers with bacterial cellulase using Brevibacillus parabrevis and Streptomyces albadancus. Some bacteria produce both bacterial cellulose and cellulase. Both cellulose and cellulase were used for the modification of natural fibers.Bacterial cellulase degrades cellulose in fiber wall structure, initiates wall stripping and fines generation. Refining then delaminate cell walls and causes wall to collapse and starts fibrillation, which provide strength to fibers.The effect of pH on the bacterial modification was also tested. Modified sunn hemp fibers were characterized with different techniques such as FTIR Spectroscopy,Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) Analysis.